Oil Price Fluctuations and Dependency Malaise: What will Engender Socio-economic Adjustments? - Oyewunmi, Olabode A. (International Journal of Energy Economics and Policy, 2018)
The fluctuations and volatility associated with international crude oil prices confirms and contradicts historical trends in varying respects. For several oil dependent African countries, the characteristic price oscillations necessitate deliberate policy and institutional adjustments. In such circumstances, it seems plausible to prioritize social and economic policy options. Veiled beneath the anticipated and unanticipated movements of oil prices lies a myriad of issues yearning for clear dissection. A fluid approach is tenable to scrutinize established and emerging questions connected with this recurring phenomenon. The ongoing geopolitical re-arrangements across various regions, uncertainties about the renewable energy agenda and policy preferences, further reinforce the importance of distilling a veritable compromise for oil revenue dependent countries. The paper entails a critique on issues impacting on the bottom-line of selected oil export centric economies and amongst other contextual dynamics. It specifically highlights matters dealing with capacity deficits, oil industry transparency and governance imperatives, policy inconsistencies, economic diversification, corporate social responsibility and optimizing governmental regulation. The paper also captures contemporary resource management perspectives, especially against the backdrop of evolving socio-economic dynamics. Applicable conceptual and theoretical views are explored, whilst practical conclusions are discussed. Keywords: crude oil; oil price; oil-dependence; socio-economic policy; Africa JEL Classifications: Q31; Q32; Q35; Q38 DOI: https://doi.org/10.32479/ijeep.6798